Entrepreneurial Intentions and Activities of Students at Portuguese Universities - 2018 - Quaresma, Rui (2021)
Nowadays, there is great interest in the subject of entrepreneurship, considering the impact it has on the economy, and so on everyone’s life. Consequently, it is an important topic for everyone: politicians, governments, labour unions, investors, employers, academics, students and citizens. This report, which is based on the data collected through the international project Global University Entrepreneurial Spirit Students' Survey (GUESSS), gives insights into the entrepreneurial intentions and activities among the 4178 participants in the GUESSS 2018 survey, from a total of 25 Portuguese higher education institutions (see the appendix for the list of the Portuguese participant institutions). In 2018, the Portuguese participation in the GUESSS project was coordinated by a team of professors from the Management Department of the School of Social Sciences, University of Évora, namely Rui Quaresma (coordinator), Jorge Casas Novas and Rui Fragoso, also researchers from Centre for Advanced Studies in Management and Economics (CEFAGE-UE). The GUESSS project was founded in 2003 at the University of St. Gallen, Switzerland, and is presently organized and managed through a cooperation between that university and the University of Bern, also in Switzerland. Currently, is one of the largest entrepreneurship research projects in the world, and the eight editions that have already taken place (2003, 2004, 2006, 2008, 2011, 2013/2014, 2016, and 2018) generated data that have been used by various researchers involved in the data collection process for publications in top journals such as the Journal of Business Venturing or Entrepreneurship Theory & Practice. We hope that the data presented and analysed in the following pages may be useful.